A Community Pediatric Camp Escape Room: An Interactive Approach to Applying Real-Life Critical Thinking Skills. (February 2021) - Spears, Syretta; Díaz, Gabriel M.; Diaz, Desiree A.
Background: Escape rooms have been utilized to incorporate teamwork, communication, policy, and procedures reinforcement, as well as clinical care. Often themed, escape rooms challenge a team of players to discover clues and sequentially solve puzzles with the ultimate task of accomplishing a specific goal in a limited time frame, fostering critical thinking. Method: This learning activity incorporateslegal implications for prelicensure nursing students in a pediatric community summer camp/after school care environment. Care andlegal implications for a minor experiencing respiratory distress was the premise of thisescape room . Outcomes: While this was not a research study, surveys were distributed for quality improvement and a deeper needs assessment related to the content and delivery of anescape room . Learners discussed the positive aspects of this activity through journal entries and a survey, noting the need for increased content related tolegal implications for the medical team. This room engaged the learner in the forward-thinking that is needed related to emergency care, Good Samaritan Act, liability for cost, and permission to treat in a time-pressured environment. Future Plans: Testing the knowledge pre-post survey related tolegal implications with implied care will be explored.